CAL evaluation: future directions - Cathy Gunn (Association for Learning Technology, 1997)
Scientific, experimental methodology was previously considered to be the only acceptable approach to educational research. Two important principles of experimental design are: • to balance individual differences within study populations and so achieve generalizable results, and • to attempt to isolate the effects of a single resource for evaluation purposes. Problems with this approach were reported in the literature of the 1970s (Elton and Laurillard, 1979; MacDonald and Jenkins, 1979) when the influence on learning of individual and contextual factors was recognized. Similar issues emerged during the 1980s and early 1990s, (Bates, 1981; Spencer, 1991) when the inability to identify which single or combined factors supported learning became a recurrent problem. It was clear that prior knowledge, approaches to learning, provision of appropriate scaffolding, complementary combinations of resources and various contextual factors all influenced the quality of learning outcomes. It was concluded that evaluations must be designed to account for these factors, rather than to balance or disregard them as was previously the norm (Kemmis, 1987, Gunn, 1995).